2005
DOI: 10.1080/17450390512331387909
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on the effect of ergot contaminated feed on performance and health of piglets and chickens

Abstract: Two dose response trials were conducted with piglets and chickens to study the effects of increasing amounts of ergot (Claviceps purpurea) with a defined alkaloid content and pattern on performance, biochemical serum characteristics and organ weights (of chickens). The ergot was mixed into the cereal-soybean meal based diets at levels of 0, 0.5, 1, 2 and 4 g/kg. The total alkaloid content of the ergot was analysed to be 2775 mg/kg and showed the following composition: ergometrine 8.1%, ergotamine 5.4%, ergocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
2
16
1
1
Order By: Relevance
“…Dänicke et al (2002) found some effects on carcass composition in a study with 56 HolsteinFriesian bulls after an exposure to mycotoxins (DON and ZON). Similar effects are described in swine and chicken exposed to ergot (Mainka et al 2005b). Mean heart and spleen weights and carcass dressing percentage were significantly higher in a group of growing-finishing pigs fed with a total daily amount of alkaloids up to 130 mg/kg LW (Mainka et al 2005a).…”
Section: Performance and Carcass Compositionsupporting
confidence: 75%
“…Dänicke et al (2002) found some effects on carcass composition in a study with 56 HolsteinFriesian bulls after an exposure to mycotoxins (DON and ZON). Similar effects are described in swine and chicken exposed to ergot (Mainka et al 2005b). Mean heart and spleen weights and carcass dressing percentage were significantly higher in a group of growing-finishing pigs fed with a total daily amount of alkaloids up to 130 mg/kg LW (Mainka et al 2005a).…”
Section: Performance and Carcass Compositionsupporting
confidence: 75%
“…Activities of enzymes in blood that are more or less indicative for hepatic lesions such as γ-glutamyl transferase (GGT), glutamate dehydrogenase (GLDH) and the less specific aspartate aminotransferase (ASAT) have been shown to respond either not at all (GLDH, GGT) or with an inconsistent and not always reproducible increase (ASAT) in piglets fed diets varying largely in the TEA between 3 and 21 mg/kg [ 16 , 17 , 18 , 19 , 20 ], whereas in calves, fattening bulls and dairy cows no effects on these enzyme activities could be detected [ 21 , 22 , 23 ]. Also to be considered in evaluating these effects are the differences in the pattern of individual alkaloids which are summed up by the TEA content, which was demonstrated to play a role for feed intake and live weight gain but was less important for liver lesions [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chez la pondeuse, 20 000 mg d'ergot/kg peuvent entraîner des baisses de production (EFSA 2005a). Mainka et al (2005) rapportent peu d'effet chez le poulet entre 1 et 21 jours d'âge en distribuant de l'aliment contenant jusqu'à 4 000 mg d'ergot/kg soit jusqu'à 11 000 µg/kg d'alcaloïdes (essentiellement ergocristine, ergométrine, ergotamines, ergocornine).…”
Section: / Ergot Et Alcaloïdes De L'ergotunclassified